2016
DOI: 10.1016/j.addr.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Strengths, weaknesses, opportunities and challenges for long acting injectable therapies: Insights for applications in HIV therapy

Abstract: Advances in solid drug nanoparticle technologies have resulted in a number of long-acting (LA) formulations with the potential for once monthly or longer administration. Such formulations offer great utility for chronic diseases, particularly when a lack of medication compliance may be detrimental to treatment response. Two such formulations are in clinical development for HIV but the concept of LA delivery has its origins in indications such as schizophrenia and contraception. Many terms have been utilised to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(107 citation statements)
references
References 147 publications
1
102
0
Order By: Relevance
“…This is especially true for existing oral anti-TB drugs, many of which lack the right balance of water solubilty, lipophilicity, half-life and potency. 16 Management of adverse effects may be more challenging with LA injectable formulations as they cannot be immediately discontinued, and the physicochemical properties that make them suitable for LA injectables also negate the option of dialysis or other strategies to remove the drug. New drug delivery technologies, such as removable solid or semi-solid implants, may alleviate many of these problems by providing options that are readily removable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is especially true for existing oral anti-TB drugs, many of which lack the right balance of water solubilty, lipophilicity, half-life and potency. 16 Management of adverse effects may be more challenging with LA injectable formulations as they cannot be immediately discontinued, and the physicochemical properties that make them suitable for LA injectables also negate the option of dialysis or other strategies to remove the drug. New drug delivery technologies, such as removable solid or semi-solid implants, may alleviate many of these problems by providing options that are readily removable.…”
Section: Discussionmentioning
confidence: 99%
“…Since parenteral delivery avoids the gastrointestinal tract and first pass metabolism, it is conceivable that the magnitude of some transporter or enzyme-mediated drug-drug interactions or pharmacogenetic variability may be less with long-acting formulations, but this remains to be seen and will require careful evaluation. 16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The strengths, weaknesses, opportunities, and challenges of LA-injectable therapies for HIV have been described excellently by Owen and Rannard. 6 The pharmacology and formulation of LA Ctg were described in a comprehensive review presented by Trezza et al 7 The authors concluded that the pharmacologic profile of Ctg has great potential for the treatment and prevention of HIV-1 infection. This drug exhibited half-life of 40 days and showed therapeutic action at a low dose.…”
mentioning
confidence: 99%